Nilai Kinerja Guru Pendidikan Jasmani Sekolah Menegah Atas Di Kota Padang - Masrun Masrun (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2022)
This research aimed to analyzed the performance of sports education teachers of Senior High school on education. The Educational system in the word had been adopted the performance assessment as an urgent mechanism to push desirable and modelling behavior among teachers as accountable object from Professional Competency, social and personality. This is considered as a survey research using descriptive method. The data is collected from 88 senior high school teacher in Padang city. The data was collected by using by questionnaire and group focused. The data analyzed by table and theme. The result of the research shows that the professional competencies in medium range categories , and social competencies in good categories. From this result, we highly recommended that assessment for the sport education teacher has to be based on the frame of development professional competencies, social and professional to enhance the education quality in Senior High School.